The Relationship between Pain and Disability in Patients with Low Back Pain - Ice Septriani Saragih; Ikhsanuddin A. Harahap; Ridha Dharmajaya (International Journal of Nursing and Health Services (IJNHS), 2020)
Low Back Pain (LBP) is a musculosceletal problem that contribute greatly to disability in general. The main complaint of patients who experience with LBP is pain. Pain is complex, multidimensional, individual and subjective. The aim of this study was to determine the relationship beetween pain and disability of low back pain. The number of samples in this study were 40 respondent. the sampling technique used is nonprobability sampling with the sampling methods was consecutive sampling. The result of this study showed that there was a significant relationship between pain (?= 0,000, p<0,05) and r= 0,663, which means it has a strong relationship between pain and disability. The conclusion of this study is there is the significant relationship between pain and disability in patients with LBP. This study recommends further studies to investigate the relationship of pain duration with disability in patient with LBP but in a larger sample.